Menelusuri Jejak Fraud: Sensitivitas Risiko Pasar dan PDB terhadap Dinamika Harga Saham di Sektor Perbankan - Ika Setya Reynata; Kristiana, Deranika Ratna; Atika Jauharia Hatta Hambali (Jurnal Akuntansi Dan Manajemen, 2024)
Since early 2020, the Indonesian economy has experienced a drastic decline in Gross Domestic Product (GDP). This decline was caused by strict mobility restrictions, which impacted banking activities in collecting and distributing funds. Banking plays an important role in economic recovery efforts by providing credit that is expected to reduce the risk of further economic decline. Thus, analysing the factors influencing banking fraud, including market risk sensitivity, gross domestic product, and stock prices, is essential.This study examines the effect of market risk sensitivity, GDP, and stock prices on banking fraud in companies listed on the Indonesia Stock Exchange from 2019 to 2023. The analysis results show that market risk sensitivity hurts banking fraud, meaning that increasing market risk sensitivity can reduce the tendency for fraud to occur. Conversely, GDP has a positive impact, where an increase in GDP tends to be followed by a rise in fraud. In addition, stock prices also hurt banking fraud, indicating that increasing stock prices can suppress fraud in banks.This study requires stricter supervision of banking practices and the importance of paying attention to macroeconomic factors in decision-making. Suggestions for further research include including additional variables, investigating the influence of other factors that may be related to fraud in the banking sector, and considering the use of more comprehensive financial theories for a more in-depth analysis.